ANALISIS KEBUTUHAN PENGEMBANGAN MODEL PEMBELAJARAN BERMAIN PERAN BERBANTUAN STORY.COM PADA PEMBELAJARAN IPAS MATERI TUGAS PEMIMPIN DAERAH KELAS III SEKOLAH DASAR - Endang Tri Anisih; Erni Suharini; Hamdan Tri Atmaja (STKIP Subang, 2024)
Technological developments have many impacts on human life which are not much different from the need for welfare. In the field of education, technological developments have had a big impact. In line with the Merdeka curriculum which is oriented towards providing ideal student learning services to the demands of the times, it provides the reality that technological sophistication can serve to bring the future closer. So learning activities become a learning medium with 21st century skills including creative, collaborative, communicative and critical. Conventional methods, such as lectures and assignments in class, only have an impossible approach in the science and science subject, regional leader assignment material, which has an impact on student motivation and interest, which can decrease. So an interesting and interactive learning method is needed so that students are motivated and active in class activities. Based on this background, this research aims to analyze the initial needs for a role-playing learning model in supporting IPAS activities regarding regional leaders' assignments with the help of the story.com platform. The research method used is a qualitative method, a qualitative method based on descriptive regulations, analysis of learning needs from teachers and students' needs regarding learning models and the media required; Qualitative methods support the collection of information by interviewing sources. Keywords: Bermain peran, Story.com, duties of regional leaders.